Analisis Kinerja Guru di TK Plus Wanaba Dalam Meningkatkan Mutu Pembelajaran - Anjani, Neng Riska; Maryono, Dicky (Jurnal Online Manajemen ELPEI, 2025)
The research entitled Analysis of Teacher Performance at Wanaba Plus Kindergarten aims to analyze the performance of teachers at Wanaba Plus Kindergarten in their efforts to improve the quality of learning at the early childhood education level. The performance of teachers in kindergarten plays an important role in the learning process, they not only function as teachers, but also as directors of child development. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The informants of this research consist of teachers, principals, at Wanaba Plus Kindergarten. The results of the study indicate that the performance of teachers at Wanaba Plus Kindergarten, some teachers have not shown good performance, this is caused by several factors, including motivation, work environment, different children's needs, and the role of parents in supporting child development. This study concludes that to improve the quality of learning, it is necessary to improve teacher competence through training and the provision of adequate facilities. The results of this study are expected to contribute to efforts to improve teacher performance and the quality of learning at Wanaba Plus Kindergarten, and can be a consideration for other early childhood education institutions.